Peran Taman Baca Masyarakat dalam Meningkatkan Keaktifan dan Literasi Masyarakat di Kp. Sasak Ds. Tegal - Sa'diyah, Yayuk Nailis Syarifatus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The existence of TBM (Community Reading Park) which is located in Kp. Sasak Ds. Tegal Kec. Kemang Kab. This Bogor will really help the community to increase the activity and literacy of the Kp community. Sasak. The purpose of this study is to provide an overview of optimizing literacy activities in increasing students' reading interest. This type of research uses qualitative research methods. Data collection techniques include observation , documentation and interviews. The research subjects include the asatidz and some residents of kp. Sasak. In addition, this Reading Garden is the flagship program of the MD-II-03 UNUSIA 2022 KKN group which resides in Madrasah Nurul Islamiyah kp. Sasak. The results of this study indicate that the TBM in Kp. This Sasak has an important role for the community, especially students in Kp. Their Sasak have containers or facilities to increase activity and literacy. With quite comfortable places and facilities, there is great hope that the MD-II-03 KKN group can provide a bridge for the community, especially children, to be more active in teaching and learning activities, namely by reading more books. In addition, with the hope that the reading garden is so that people can add insight and broader knowledge. TBM Kp. Sasak is also divided into two places in Rt.10 Rw.08 and Madrasah Nurul Islamiyah. Keywords: Reading Gardens, Society, Activity and Literacy.